2023
DOI: 10.1055/a-2018-4845
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Sensory-Motor Neuropathy Mimicking CIDP as Predominant Presentation of PDH Deficiency

Abstract: Introduction: PDH deficiency (OMIM # 312170) is a relatively common mitochondrial disorder, caused by mutations in the X-linked PDHA1 gene and presenting with a variable phenotypic spectrum, ranging from severe infantile encephalopathy to milder chronic neurological disorders. Isolated peripheral neuropathy as predominant clinical presentation is uncommon. Results: We report on a patient, now 21 years old, presenting at the age of 2 years with recurrent symmetric weakness as first symptom of a PDH deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The mutation is deleterious (CADD PHRED score 24.4; Revel score 0.82) and involved a residue highly conserved through evolution from human to zebrafish localized in the conserved tubulin C-terminal protein domain (IPR023123). Using freely available tools to assess the impact of missense variants in protein stability and assembly [ 17 ], we showed that the p.Glu415Lys variant had a likely destabilizing effect (ΔΔG − 0.61) on α-tubulin stability (Fig. 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…The mutation is deleterious (CADD PHRED score 24.4; Revel score 0.82) and involved a residue highly conserved through evolution from human to zebrafish localized in the conserved tubulin C-terminal protein domain (IPR023123). Using freely available tools to assess the impact of missense variants in protein stability and assembly [ 17 ], we showed that the p.Glu415Lys variant had a likely destabilizing effect (ΔΔG − 0.61) on α-tubulin stability (Fig. 1 B).…”
Section: Resultsmentioning
confidence: 99%